Update 2015 on Target Fabrication Requirements for NIF Layered Implosions, with Emphasis on Capsule Support and Oxygen Modulations in GDP. (1st September 2016) - Haan, S. W.; Clark, D. S.; Baxamusa, S. H.; Biener, J.; Hopkins, L. Berzak; Bunn, T.; Callahan, D. A.; Carlson, L.; Dittrich, T. R.; Edwards, M. J.; Hammel, B. A.; Hamza, A.; et al.
Abstract: Experiments and analysis in the 3 years since the 2012 Target Fabrication Meeting have resulted in significant improvement in understanding of the requirements for high-performance layered implosions. Three issues have been identified that significantly degrade the performance of the implosions as they were originally configured for National Ignition Facility experiments: capsule support system, time-dependent radiation asymmetry, and transverse oxygen nonuniformity in the glow discharge polymer (GDP) ablator. Analyses suggest that the shortfalls in these three areas can explain the degraded performance of the National Ignition Campaign implosions. We present the status of work toward curing these three problems in the standard GDP ablator/gold hohlraum configuration as they affect target fabrication priorities. We also summarize the prospects for alternate ablators that might reduce these degradation mechanisms.